Potential of hydrogen production from intermittent renewable energy resources in different locations of Nigeria: Technical, economic and environmental perspective - Richard Oladayo Olarewaju; Ayodeji Samson Olatunji Ogunjuyigbe; Temitope Raphael Ayodele; Samson Oladayo Ayanlade; Yuming Feng; Chaoran Liu (Global Energy Interconnection)
In this study, ten wind turbines and fourteen solar photovoltaic (SPV) modules were employed to compare the potential of hydrogen production from wind and solar energy resources in the six geopolitical zones of Nigeria. The amount of hydrogen produced was considered as a technical parameter, cost of hydrogen production was considered as an economic index, and the amount of carbon (IV) oxide saved from the use of diesel fuel was considered as an environmental index. The results reveal that ENERCON E-40 turbine yields the highest capacity factor in Lagos, Jos, Sokoto, Bauchi and Enugu sites while FUHRLAENDER, GMBH yields the highest capacity factor in Delta. The mean annual hydrogen production from wind ranged from 2.05 tons/annum at site S6 (Delta) to 17.33 tons/annum at site S3 (Sokoto), and the mean annual hydrogen production from SPV ranged from 64.33 tons/annum at sites S1 (Lagos) to 140.28 tons/annum at site S6 (Delta). The cost of hydrogen production from wind was 6.3679 and 25.9007$/kg for sites S3 and S6, respectively, and the cost of hydrogen production from SPV was 5.6659 and 6.1206$/kg for sites S3 and S1, respectively. The amount of CO2 saved annually from wind-based hydrogen generation was 137,267 kg/year in site S6 and 504,180 kg/year in site S3, and was used to produce electricity via fuel cells. The amount of CO2 saved using hydrogen produced from SPV was 615,400 kg/year and 1,341,899 kg/year in sites S1 and S6, respectively. The results also revealed that 75.55%, 88.93%, 80.28%, 80.54%, 85.65%, 98.53% more hydrogen could be produced from SPV for sites S1–S6, respectively, compared to the wind resources. This study serves as a source of reliable technical information to relevant government agencies, policy makers and investors in making informed decisions on optimal investment in the hydrogen economy of Nigeria.